Surgical and transcatheter aortic valve replacement align survival with general population expectations: insights from standardized mortality ratios - Boute, Marin; De Azevedo, David; de Terwangne, Christophe; Pouleur, Anne-Catherine; Pasquet, Agnès; Gerber, Bernhard L.; de Kerchove, Laurent; Beauloye, Christophe; Kefer, Joëlle; Maes, Frédéric; Pierard, Sophie; Vancraeynest, David (Frontiers in Cardiovascular Medicine, 2025)
BackgroundComparative long-term survival outcomes between transcatheter (TAVR) and surgical (SAVR) aortic valve replacement remain debated. While randomized controlled trials support TAVR's non-inferiority, real-world data indicate the opposite. Comparing SAVR and TAVR patients with matched reference populations may reduce bias from direct comparisons. We compared the 5-year overall survival rates of SAVR, non-frail TAVR, and frail TAVR patients with those of matched general population standards.MethodsAll patients who underwent bioprosthetic SAVR or TAVR at a tertiary hospital from 2012 to 2021 were included. Based on intervention type and Clinical Frailty Scale, patients were divided into three groups: SAVR, non-frail TAVR, and frail TAVR. Survival was compared to individual-level age- and sex-matched general population data using standardized mortality ratios (SMRs).ResultsThe cohort included 939 SAVR, 328 non-frail TAVR, and 121 frail TAVR patients, with mean ages of 73.6, 85.3, and 85.6 years, and median EuroSCORE II values of 1.9%, 4.0%, and 5.2%, respectively. SAVR and non-frail TAVR patients had survival rates comparable to those of the reference population [SMR = 0.93 [0.76–1.14]; p = 0.437 and SMR = 0.94 [0.76–1.15]; p = 0.468]. Conversely, frail TAVR patients faced a 40% increased mortality risk compared with their reference population [SMR = 1.40 (1.04–1.88); p = 0.012].ConclusionsIn non-frail patients, TAVR and SAVR both restore life expectancy to general population standards. For frail TAVR patients, the lower survival rate highlights frailty's important prognostic impact and underlines the ongoing challenge of refining patient selection to avoid futility.